MINING SUPERVISION IN PROTECTED FOREST AREAS IN INDONESIA - Nugraha, Ridho Putra; Sebianto, Hadi; Ginting, Valentino; Ramadhan, Muhammad Gusti; Putri, Sinta Amelia (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
This research aims to analyze licensing related to mining activities in protected forest areas in Indonesia. They are using normative juridical methods with statutory and conceptual approaches. The results of this study can conclude that although there is a comprehensive legal framework, implementation, and law enforcement still face various challenges, including a lack of coordination between institutions, weak law enforcement, and conflicts of interest between environmental protection and exploitation of natural resources. Dispute resolution can be pursued through out-of-court / nonlitigation. The settlement of ecological disputes outside the court can be done by mediation or arbitration using the services of mediators and arbitrators who help resolve environmental disagreements. Settlement of environmental disputes through court legal means is carried out by filing an